2021
DOI: 10.2196/26963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-focused Augmented Reality on Health Perceptions During the COVID-19 Pandemic: A Web-Based Between-Subject Experiment

Abstract: Background Self-focused augmented reality (AR) technologies are growing in popularity and present an opportunity to address health communication and behavior change challenges. Objective We aimed to examine the impact of self-focused AR and vicarious reinforcement on psychological predictors of behavior change during the COVID-19 pandemic. In addition, our study included measures of fear and message minimization to assess potential adverse reactions to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…These studies were conducted during the COVID-19 pandemic, a time when personal and public concerns for health have become more pronounced. These studies demonstrate the potential of AR as a medium that encourages non-experts to assess health risks using the affordances of immersive design that has been shown to impact health perceptions (Regenbrecht et al, 2011;Jung et al, 2019;Ku et al, 2021;Seals et al, 2021). While study 1 visualizes omic information to users on their personal bodies, study 2 overlays omic information to users on the personal environment of the kitchen.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…These studies were conducted during the COVID-19 pandemic, a time when personal and public concerns for health have become more pronounced. These studies demonstrate the potential of AR as a medium that encourages non-experts to assess health risks using the affordances of immersive design that has been shown to impact health perceptions (Regenbrecht et al, 2011;Jung et al, 2019;Ku et al, 2021;Seals et al, 2021). While study 1 visualizes omic information to users on their personal bodies, study 2 overlays omic information to users on the personal environment of the kitchen.…”
Section: Introductionmentioning
confidence: 87%
“…Ku et al (2021) found the AR game, Pokemon-Go, to promote mental and physical health as its game design and AR functionality encourage the formation and maintenance of social relationships and outdoor physical activity. Empirical studies have evaluated the impact of self-focused AR (layering health risks onto the body) on health risk perceptions, finding an increase in perceived threat susceptibility, severity, negative affect, and behavioral intentions when compared to control conditions (Jung et al, 2019;Seals et al, 2021).…”
Section: Ar Interventions For Personal Healthmentioning
confidence: 99%
See 3 more Smart Citations